High-Resolution Spin-Resolved Photoemission Spectrometer and the Rashba Effect in Bismuth Thin Films - Takayama, Akari (Springer, 2016)
In this thesis, the author has developed a high-resolution spin-resolved photoemission spectrometer that achieves the world-best energy resolution of 8 meV. The author has designed a new, highly efficient mini Mott detector that has a large electron acceptance angle and an atomically flat gold target to enhance the efficiency of detecting scattered electrons.